Gefitinib inhibits the cross‐talk between mesenchymal stem cells and prostate cancer cells leading to tumor cell proliferation and inhibition of docetaxel activity1. Issue 5 (14th March 2013) - Borghese, Cinzia; Cattaruzza, Lara; Pivetta, Eliana; Normanno, Nicola; De Luca, Antonella; Mazzucato, Mario; Celegato, Marta; Colombatti, Alfonso; Aldinucci, Donatella
Abstract Increasing evidence suggests that bone marrow derived mesenchymal stem cells (BM‐MSCs) are recruited into the stroma of developing tumors where they contribute to progression by enhancing tumor growth and metastasis, or by inducing anticancer‐drug resistance. Prostate cancer cells secrete ligands of epidermal growth factor receptor (EGFR) and EGFR signaling could play an important role in the cross‐talk between mesenchymal stem cells and prostate cancer cells. In this study, we showed that treatment of human primary MSCs with conditioned medium (CM) derived from the bone metastatic PC3 carcinoma cells (PC3‐CM) resulted in: a significant activation of EGFR; increased proliferation; increased osteoblastic but decreased adipocitic differentiation; inhibition of senescence induced by serum starvation; increased CCL5 secretion. These activities were significantly inhibited in the presence of the EGFR tyrosine kinase inhibitor gefitinib. PC3‐CM directly inhibited osteoclastogenesis as well as the ability of osteoblasts to induce osteoclast differentiation. The increased MSCs migration by PC3‐CM and PC3 cells was partially mediated by CCL5. MSC‐CM increased the formation of colonies by PC3 cells and inhibited the anti‐proliferative activity of Docetaxel. Activation of EGFR expressed on MSCs by PC3‐CM enhanced their capability to increase PC3 cells proliferation and to inhibit Docetaxel activity. These findings, by showing that the tumor‐promoting interactions between PC3 cells and MSCs are mediated, at least in part, by EGFR, suggest a novel application of the EGFR‐tyrosine kinase inhibitors in the treatment of prostate cancer. J. Cell. Biochem. 114: 1135–1144, 2013. © 2012 Wiley Periodicals, Inc.